Fungsi dan Struktur Mantra Pengobatan Sakit Perut di Desa Jomboran Kecamatan Wuryantoro Kabupaten Wonogiri Provinsi Jawa - Paranti, Paranti (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
This study aims to examine the structure and function of a stomachache healing mantra used by the community of Jomboran Village, Pulutan Wetan, Wuryantoro District, Wonogiri Regency, Central Java. The material object of this research is the oral utterance of the healing mantra as performed by a traditional practitioner within the context of healing practices. This study employs a qualitative approach with a descriptive method and applies a literary structuralism approach, specifically poetic structuralism, contextualized within oral literature. Data were collected through observation, in-depth interviews, and audio recording of the mantra utterances, which were subsequently transcribed and analyzed. The analysis focuses on the structural elements of the mantra, including sound patterns (assonance, alliteration, and rhyme), diction, and concrete words, while also considering the context of performance and the ritual function of the mantra as a performative oral text. The results indicate that the stomachache healing mantra possesses a poetic structure built through repetition, rhythm, and harmonious sound patterns that function to strengthen its suggestive power and magical effect. The diction and concrete words used emphasize elements of spirituality and healing symbolism. The functions of the mantra include healing, spiritual, psychological effects, and the preservation of local cultural traditions. The novelty of this study lies in its examination of healing mantras as performative oral literature by integrating poetic structural analysis with ritual function based on oral data from a local context in which the number of practitioners is increasingly limited. === Penelitian ini bertujuan untuk mengkaji struktur dan fungsi mantra pengobatan sakit perut yang digunakan oleh masyarakat Desa Jomboran, Pulutan Wetan, Kecamatan Wuryantoro, Kabupaten Wonogiri, Jawa Tengah. Objek material penelitian ini adalah tuturan mantra pengobatan yang dituturkan oleh penutur dalam konteks praktik pengobatan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, serta menerapkan pendekatan strukturalisme sastra dalam pengertian strukturalisme puitik yang dikontekstualkan pada sastra lisan. Data diperoleh melalui observasi, wawancara mendalam, dan perekaman tuturan mantra, yang selanjutnya ditranskripsikan dan dianalisis. Analisis dilakukan dengan mengkaji unsur-unsur struktur mantra, meliputi bunyi (asonansi, aliterasi, dan rima), diksi, serta kata konkret, dengan tetap mempertimbangkan konteks penuturan dan fungsi ritual mantra sebagai teks performatif lisan. Hasil penelitian menunjukkan bahwa mantra pengobatan sakit perut memiliki struktur puitik yang dibangun melalui pengulangan, ritme, dan keharmonisan bunyi yang berfungsi memperkuat daya sugestif dan efek magis. Diksi dan kata konkret yang digunakan menegaskan unsur spiritualitas dan simbol penyembuhan. Fungsi mantra meliputi fungsi penyembuhan, fungsi spiritual, efek psikologis, serta fungsi pelestarian tradisi budaya masyarakat setempat. Kebaruan penelitian ini terletak pada pengkajian mantra pengobatan sebagai sastra lisan performatif yang mengintegrasikan analisis struktur puitik dan fungsi ritual berbasis data tuturan lisan dari konteks lokal yang penuturnya semakin terbatas.